THE EFFECTIVENESS OF HYDROLYZED VCO CREAM ON VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) EXPRESSION AND COLLAGEN THICKNESS FOR HEALING 2ND DEGREE BURNS INJURY IN WISTAR RATS - Fahmi Syarif; Neni Susilaningsih; Yuriz Bakhtiar (RSUP Dr. Kariadi, 2021)
ABSTRACT Burn wounds remain a serious problem in several countries. The presence of burn wounds might trigger local or in severe cases also triggers systemic response. Immediate treatment is required to prevent further tissue damage. Silver sulfadiazine cream is commonly used as a burn therapy. However, long-time usage might cause negative side effects. Several effective alternatives with better safety are opted, including virgin coconut oil (VCO). Originating from Cocos nucifera, commonly known as the coconut plant, VCO is a product that contains a lot of beneficial substances, such as lauric acid, polyphenol, and alpha-tocopherol. Hydrolyzed VCO can be an alternative to topical drugs in second-degree burns as it increases Vascular Endothelial Growth Factor (VEGF) expression and collagen thickness in the burn wound healing phase. This randomized post-test only with parallel-group experiment was done using Wistar rats induced to a second-degree burn. The effect of 70% and 100% on second-degree burn healing, measured by hydrolyzed VCO on VEGF expression and collagen thickness was observed between 6 and 12 days of therapy. VEGF expression and collagen expression increased higher in groups treated with 70% and 100% hydrolyzed VCO compared with the control group treated with base cream.